2013
DOI: 10.1111/aos.12110
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green angiographic and optical coherence tomographic findings support classification of polypoidal choroidal vasculopathy into two types

Abstract: . Purpose:  We assessed the characteristic indocyanine green angiographic (ICGA) and spectral domain optical coherence tomographic (SD‐OCT) findings of two types of polypoidal choroidal vasculopathy (PCV), distinguishable by different filling patterns on ICGA. Methods:  Thirty‐one eyes with PCV were classified into types 1 and 2 based on ICGA findings of either the presence or absence of both a feeder and a draining vessel. Characteristic ICGA findings were evaluated for each type of PCV. Spectral domain optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 31 publications
5
87
0
6
Order By: Relevance
“…Recent studies have described the subclassification of PCV regarding the presence or absence of BVN (as feeder vessels for the polyp lesions) found by ICGA [57,58,59]. Thus, PCV with apparent BVN is called ‘type 1 PCV' or ‘polypoidal CNV', whereas the one with no or only faint BVN is called ‘type 2 PCV' or ‘typical PCV' (fig.…”
Section: Angiographic Imagingmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have described the subclassification of PCV regarding the presence or absence of BVN (as feeder vessels for the polyp lesions) found by ICGA [57,58,59]. Thus, PCV with apparent BVN is called ‘type 1 PCV' or ‘polypoidal CNV', whereas the one with no or only faint BVN is called ‘type 2 PCV' or ‘typical PCV' (fig.…”
Section: Angiographic Imagingmentioning
confidence: 99%
“…Recent studies demonstrated that these 2 angiographic subtypes of PCV showed differences in their clinical course, genetic susceptibility and response to therapy. Type 1 PCV usually has larger lesion sizes due to the larger and more distinct BVN, smaller polyp size on ICGA, smaller choroidal thickness [57,58,59] and lower response to photodynamic therapy (PDT) as compared to type 2 PCV [60]. …”
Section: Angiographic Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…This represents the last, most advanced stage of the spectrum of pachychoroid disease of the macula, which can be displayed with the aid of ICGA (obr. 6C) [20,22]. PCV has a predilection for incidence in people of Asian or African race, but may also affect individuals of the white race.…”
Section: Polypoid Choroidal Vasculopathymentioning
confidence: 99%